1994
DOI: 10.1016/0741-5214(94)90178-3
|View full text |Cite
|
Sign up to set email alerts
|

The durability of different reconstructive techniques for atherosclerotic renal artery disease

Abstract: Because extraanatomic bypass grafting can provide long-term results equivalent to aortorenal bypass grafting, the choice among techniques for RAR in patients with diffuse atherosclerosis should be based on both technical and operative safety considerations, rather than adherence to aortorenal bypass grafting as an inherently superior technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(38 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…In 1994, Cambria et al 9 reported on the surgical revascularization of 323 atherosclerotic renal arteries in 285 patients, 47% of whom had normal renal function (baseline creatinine Յ1.5 mg/dL). The operative mortality was 5.6% (8.1% when the procedure involved the aorta and 4.1% in procedures that avoided the aorta).…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, Cambria et al 9 reported on the surgical revascularization of 323 atherosclerotic renal arteries in 285 patients, 47% of whom had normal renal function (baseline creatinine Յ1.5 mg/dL). The operative mortality was 5.6% (8.1% when the procedure involved the aorta and 4.1% in procedures that avoided the aorta).…”
Section: Discussionmentioning
confidence: 99%
“…Early graft failure (2-10%) is highly associated with perioperative death and is most often related to technical problems. 92,101 Graft patency has generally been favorable, with 5-year combined patency rates of 82-94%. [100][101][102] Late failures are generally related to intimal hyperplasia or progressive atherosclerosis.…”
Section: Renal Artery Revascularizationmentioning
confidence: 99%
“…92,101 Graft patency has generally been favorable, with 5-year combined patency rates of 82-94%. [100][101][102] Late failures are generally related to intimal hyperplasia or progressive atherosclerosis. Nephrectomy (or percutaneous embolization) remains an option for patients with unilateral stenoses and uncontrollable HTN that cannot be successfully revascularized.…”
Section: Renal Artery Revascularizationmentioning
confidence: 99%
“…A complete recovery is possible only in 15-58% of all patients, improvement in 21-75%, and persisting higher blood pressure values are observed in 5-38% of patients. Much worse results in this group of patients are connected with the frequent coexistence of primary arterial hypertension [3].…”
Section: Discussionmentioning
confidence: 99%